Unconventional Technique for Producing Borosilicate Glass Foam - Lucian Paunescu; Marius Florin Dragoescu; Sorin Mircea Axinte; Felicia Cosmulescu (Journal La Multiapp, 2020)
The study aims to test an advanced technique but insufficiently valued in the world in the process of experimental manufacture of borosilicate glass foam. It is about the unconventional technique of heating solids by using the microwave radiation converted into heat. The experimental equipment on which the tests were performed was a 0.8-kW microwave oven commonly used in the household with constructive adaptations to be operational at high temperature. The adopted manufacturing recipe was composed of borosilicate glass waste with the addition of calcium carbonate, boric acid and water in different weight proportions. The material was sintered at 829-834 ºC by predominantly direct microwave heating and the optimal foamed product had characteristics similar to those manufactured by conventional techniques (apparent density of 0.33 g/cm3, thermal conductivity of 0.070 W/m•K, compressive strength of 3.1 MPa and a homogeneous microstructure with pore size between 0.7-1.0 mm). The energy efficiency of the unconventional manufacturing process was remarkable, the specific energy consumption being only 0.92 kWh/kg.